Common and rare variant association analyses in amyotrophic lateral sclerosis identify 15 risk loci with distinct genetic architectures and neuron-specific biology - Van Rheenen, Wouter; van der Spek, Rick A. A.; Bakker, Mark K.; van Vugt, Joke J. F. A.; Hop, Paul J.; Zwamborn, Ramona A. J.; de Klein, Niek; Westra, Harm-Jan; Bakker, Olivier B.; Deelen, Patrick; Shireby, Gemma; Hannon, Eilis; et al. (Nature genetics, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with a lifetime risk of one in 350 people and an unmet need for disease-modifying therapies. We conducted a cross-ancestry genome-wide association study (GWAS) including 29,612 patients with ALS and 122,656 controls, which identified 15 risk loci. When combined with 8,953 individuals with whole-genome sequencing (6,538 patients, 2,415 controls) and a large cortex-derived expression quantitative trait locus (eQTL) dataset (MetaBrain), analyses revealed locus-specific genetic architectures in which we prioritized genes either through rare variants, short tandem repeats or regulatory effects. ALS-associated risk loci were shared with multiple traits within the neurodegenerative spectrum but with distinct enrichment patterns across brain regions and cell types. Of the environmental and lifestyle risk factors obtained from the literature, Mendelian randomization analyses indicated a causal role for high cholesterol levels. The combination of all ALS-associated signals reveals a role for perturbations in vesicle-mediated transport and autophagy and provides evidence for cell-autonomous disease initiation in glutamatergic neurons.
Autoren: Wouter van Rheenen, Jochen H. Weishaupt, David Brenner, Marcella Rietschel [und 188 weitere]
Gesehen am 24.08.2022